2019
DOI: 10.21432/cjlt27849
|View full text |Cite
|
Sign up to set email alerts
|

From studio practice to online design education: Can we teach design online? | De l’enseignement pratique en studio à l’enseignement en ligne : peut-on enseigner le design en ligne ?

Abstract: Digital technology is reshaping the way higher education subjects are taught, including design. Various design disciplines use studio teaching as a pedagogy to educate students for professions in art and design. Studio teaching bases a high premium on face-to-face interactions which guide learning through dialogue and feedback on individual work. Many design educators believe it is difficult or even impossible to teach design online because of studio-based interactions. Is design one of those disciplines that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…It has been determined that the satisfaction level of 4th graders who have been educated with the traditional method for a longer period of time is low (Table 2). The results obtained from the findings related to satisfaction and indicating that the lower classes are at a higher level of satisfaction from the blackboard application according to the internet connection data also confirm the studies (Table 2, Table 4) [14], [29]. As seen in Table 3, it is concluded that the achievements and grade levels of interior architecture students who take project courses through the blackboard application are related.…”
Section: Resultssupporting
confidence: 75%
“…It has been determined that the satisfaction level of 4th graders who have been educated with the traditional method for a longer period of time is low (Table 2). The results obtained from the findings related to satisfaction and indicating that the lower classes are at a higher level of satisfaction from the blackboard application according to the internet connection data also confirm the studies (Table 2, Table 4) [14], [29]. As seen in Table 3, it is concluded that the achievements and grade levels of interior architecture students who take project courses through the blackboard application are related.…”
Section: Resultssupporting
confidence: 75%
“…Those approaches emphasised the need for contextualized, adaptable, and flexible programs and environments, organized to meet the different needs for knowledge and competences. Fleischmann (2019Fleischmann ( , 2020aFleischmann ( , 2020b for instance, contributed with different studies and reviewed different approaches to the virtual, blended learning alternative for the design studio pedagogy. The author considered that overall students acknowledged positive aspects, such as flexibility of watching the lessons when they had time, enhanced self-management capabilities, but she identified the demotivation felt by students in the final weeks of the course, due to a lack of interaction with the lecturer.…”
Section: Fashion and Design Within The Technological Immersivenessmentioning
confidence: 99%
“…Given these new circumstances and even the ability to reach more students through an online alternative, online delivery should be explored more deeply as there are different expectations from both instructors and students. A previous study byFleischmann (2019) shared findings of two first-year graphic design studio courses that were delivered online. The positive aspects were "provided flexibility […] beneficial for individual learning style […] high quality of learning content […] speed of communication and feedback; responsiveness of instructor" (p. 9).…”
mentioning
confidence: 76%
“…"Much thought, preparation, and post-production was spent on the creation of the online lectures. Considerations included how to make videos engaging, informative, and short enough to avoid boring students with short attention spans" (Fleischmann, 2019). A lot of the brunt of the work falls on the instructor who may not have the necessary technical skills to produce class content; therefore, having support from institutions, in the form of video producers and time, is paramount for the development of successful online courses.…”
Section: Make More To Understand Morementioning
confidence: 99%
See 1 more Smart Citation